Russia on the Path Towards a New Technology-Industrial Policy: Exciting Prospects and Fatal Traps - Yuri Simachev; Mikhail Kuzyk; Boris Kuznetsov; Evgeniy Pogrebnyak (Foresight and STI Governance, 2014)
The article aims to discuss the practical problems and inconsistencies of industrial policy in Russia since 2000, to analyze positive and negative experiences, and to draw up some lessons which are essential for a new technology-industrial policy.